Pengaruh Pengembangan Karir, Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT PNM Meekar Syariah Wilayah Aceh Barat - Sinambela, Lola Novelda; M, Murtaza (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to determine the influence of career development, work motivation and work discipline on employee performance at PT PNM Meekar Syariah West Aceh Region. The data collection technique in this research is by observation, interviews and questionnaires. This research involved 77 employees at PT PNM Meekar Syariah West Aceh Region. The data analysis used was the partial t test and F anava test. The results of the research show that the sig value for the career development variable (X1) is 0.000, meaning that career development (X1) influences employee performance. Furthermore, the sig value for the work motivation variable (X2) is 0.006, meaning work motivation (X2) has an effect on employee performance and the sig value for the work discipline variable (X3) is 0.381, meaning the discipline variable (X3) has no effect on employee performance. Meanwhile, simultaneously using the ANOVA test, the sig value is 0.000b, this means that overall career development, motivation and work discipline influence employee performance.